2020
DOI: 10.11604/pamj.2020.37.53.24994
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of psychiatric morbidity, comorbid anxiety and depression among medical students in public and private tertiary institution in a Nigerian state: a cross-sectional analytical study

Abstract: Introduction the study assessed the prevalence and factors associated with psychiatric morbidity (an array of psychological disorders), and comorbid anxiety and depression among medical students in Ekiti State, Nigeria. Methods a cross-sectional study of medical students in two universities (one public and one private) in Ekiti state was conducted. A semi-structured questionnaire with adapted questions from the General Health Questionnaire and Hospital Anxiety and Depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
3
12
2
Order By: Relevance
“…The present study found that perception of academic performance and the experience of academic failure had significant relationships with depression among the study population. This finding is similar to previous studies in both medical and non-medical students (Nwobi et al, 2009;Aniebue & Onyema, 2008;Falade et al, 2020;Khan et al, 2018). , Falade et al 2020 in a study involving 944 medical students found a 25.0% prevalence of psychiatric morbidity among the respondents, and associated independent factors also included; being a student of a private institution, average academic performance, and below-average academic performance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study found that perception of academic performance and the experience of academic failure had significant relationships with depression among the study population. This finding is similar to previous studies in both medical and non-medical students (Nwobi et al, 2009;Aniebue & Onyema, 2008;Falade et al, 2020;Khan et al, 2018). , Falade et al 2020 in a study involving 944 medical students found a 25.0% prevalence of psychiatric morbidity among the respondents, and associated independent factors also included; being a student of a private institution, average academic performance, and below-average academic performance.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is similar to previous studies in both medical and non-medical students (Nwobi et al, 2009;Aniebue & Onyema, 2008;Falade et al, 2020;Khan et al, 2018). , Falade et al 2020 in a study involving 944 medical students found a 25.0% prevalence of psychiatric morbidity among the respondents, and associated independent factors also included; being a student of a private institution, average academic performance, and below-average academic performance. Using a cross-sectional design, Khan et al (2018) collected data on several stressors psychiatric morbidities from 379 students.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar higher anxiety scores were found in medical students in the private sector of Karachi, Pakistan and Nigeria. 8,26 This could be due to pressure of studies and passing exams, higher amount of fees paid by the students, increased pressure from parents, as well as pressure of living up to the expectations of the family.…”
Section: Discussionmentioning
confidence: 99%